Protosticta curiosa Fraser, 1934 and its synonyms in Vietnam and China (Odonata: Platystictidae) - Kompier, Tom (Zootaxa, 2018)
Protosticta zhengi Yu & Bu, 2009 and Protosticta albifrons Kompier, 2016 are shown to be synonyms of P. curiosa Fraser, 1934. The general distribution of P. curiosa is discussed and the key to the P. curiosa-group of Protosticta species for Vietnam is updated.